Justifying parameters for the automatic servo control system of a rotary plate vacuum pump in the milking machine - Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли; Paliy, Andriy; Палій, Андрій Павлович; Kis, Viktor; Кісь, Віктор Миколайович; Milenin, Andriy; Міленін, Андрій Миколайович; Ishchenko, Katerina; Іщенко, Катерина; Paliy, Anatoliy; Палій, Анатолій Павлович; et al. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР", Україна, 2022)
The scientific task to improve energy efficiency and ensure the process of vacuum regime stabilization in the operation of milking machines has been solved. A mathematical model of the process of functioning of the servo control system of a rotary plate vacuum pump was built; the numerical modeling of its workflow was carried out. This paper reports the results of experimental studies on the influence of the regime parameters of the rotary plate vacuum pump on the efficiency of its operation, as well as the results of experimental research on the servo control system for the rotary plate vacuum pump. The operational process of the rotary plate vacuum pump HB-1200 for a milking machine was investigated. The influence of mode parameters (rotor speed n and vacuum pressure P) on the performance of the vacuum pump, Qa, vacuum pressure fluctuation, ΔP, and the power consumption of the vacuum pump drive, Np, has been determined. The servo control system of the rotary plate vacuum pump was experimentally investigated based on the developed algorithms of its operation. In a generally accepted algorithm, vacuum fluctuation increases with increasing an airflow rate: at ΔQa=45 l/min – ΔP=2.3 kPa; at ΔQa=90 l/min – ΔP=4.6 kPa; at ΔQa=135 l/min – ΔP=6.4 kPa. Unlike the generally accepted one, the developed algorithm enables a stable vacuum mode with the largest vacuum fluctuation being ΔP=2.4 kPa. For the first time, the functional dependence of the influence of the regime parameters of the rotary plate vacuum pump with its automatic servo control system on the stability of the vacuum regime of a milk-vacuum system in the milking machine was established. The results can be applied when improving milking machines in terms of ensuring the stabilization process of the vacuum regime. Вирішено наукове завдання щодо підвищення енергоефективності та забезпечення процесу стабілізації вакуумного режиму в роботі доїльних апаратів. Побудовано математичну модель процесу функціонування системи сервокерування роторно-пластинчастого вакуумного насоса; проведено чисельне моделювання його робочого процесу. У роботі наведені результати експериментальних досліджень впливу режимних параметрів роторного вакуумного насоса на ефективність його роботи, а також результати експериментальних досліджень системи сервокерування роторного вакуумного насоса. Досліджено процес роботи пластинчасто-роторного вакуумного насоса НВ-1200 для доїльного апарату. Визначено вплив режимних параметрів (частота обертання ротора n і вакуумний тиск P) на продуктивність вакуумного насоса Qa, коливання вакуумного тиску ΔP та споживану потужність приводу вакуумного насоса Np. Експериментально досліджено систему сервокерування роторно-пластинчастого вакуумного насоса на основі розроблених алгоритмів його роботи. У загальноприйнятому алгоритмі флуктуація вакууму зростає зі збільшенням витрати повітря: при ΔQa=45 л/хв – ΔP=2,3 кПа; при ΔQa=90 л/хв – ΔP=4,6 кПа; при ΔQa=135 л/хв – ΔP=6,4 кПа. На відміну від загальноприйнятого, розроблений алгоритм забезпечує стабільний режим вакууму з найбільшою флуктуацією вакууму ΔP=2,4 кПа. Вперше встановлено функціональну залежність впливу режимних параметрів роторно-пластинчастого вакуумного насоса з системою автоматичного сервокерування на стабільність вакуумного режиму молоко-вакуумної системи в доїльному апараті. Отримані результати можуть бути застосовані при вдосконаленні доїльних апаратів у частині забезпечення процесу стабілізації вакуумного режиму.
Обґрунтування параметрів системи автоматичного сервокерування роторно-пластинчастого вакуумного насоса доїльного апарату
Keywords: milking machine; доїльний апарат; vacuum pump; вакуумний насос; vacuum pressure; вакуумний тиск; vacuum fluctuation; коливання вакууму; servo control; сервоуправління